CCS - Failing to Pass Decision Gates - Magne Emhjellen; Petter Osmundsen (Center for Economic Studies and ifo Institute (CESifo), 2013)
Socio-economic criteria for climate projects have been used in analysing the value of the climate benefit of a reduction in CO2. These reports are optimistic, yet CCS demonstration plants are not implemented as expected. Little attention has been devoted to profitability assessments based on commercial considerations. Economic valuation of climate projects, seen from the perspective of the commercial companies which are to implement the projects, is the subject of this article. We examine key economic parameters of 27 oil and gas projects and compare it to a CCS project. We find that the CCS project ranks the lowest and is unlikely to be implemented by a private company. Our findings may explain why it is hard for oil companies to justify climate projects in their portfolios.
Keywords: Q38; Q53; Q54; 330; climate projects; decision analysis; CO2